(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the impact of information technologies on the psychological state of today’s youth. The positive and negative effects of modern digital technologies, in particular the Internet, social networks, and mobile devices, on young people’s consciousness, behavior, communication culture, and emotional state are highlighted.